2022
DOI: 10.1101/2022.08.23.505039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linear motif specificity in signaling through p38α and ERK2 mitogen-activated protein kinases

Abstract: Mitogen-activated protein kinase (MAPK) cascades are essential for eukaryotic cells to integrate and respond to a wide array of stimuli. Maintaining specificity in signaling through MAPK networks is key to coupling specific inputs to appropriate cellular responses. One way that MAPKs achieve specificity is through transient interactions with docking sites: short linear motifs found in MAPK substrates, regulators, and scaffolds. Docking sites bind to a conserved groove located in the catalytic domain of all MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…More recently, studies have begun to use techniques such as deep mutational scanning (DMS) to study the impact of large libraries of mutations on protein stability and function in vivo (Fowler and Fields 2014). Methods such as protein complementation assays (Tarassov et al 2008;Michnick et al 2016) have also successfully been used to measure the in vivo binding strength of libraries of mutants in yeast (Diss and Lehner 2018;Dionne et al 2021;Faure et al 2022;Robles et al 2023;Bendel et al 2023;Dibyachintan et al 2024). For example, a recent study showed the effect on binding of combining mutations in a PDZ domain and its binding motif (Zarin and Lehner 2024).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies have begun to use techniques such as deep mutational scanning (DMS) to study the impact of large libraries of mutations on protein stability and function in vivo (Fowler and Fields 2014). Methods such as protein complementation assays (Tarassov et al 2008;Michnick et al 2016) have also successfully been used to measure the in vivo binding strength of libraries of mutants in yeast (Diss and Lehner 2018;Dionne et al 2021;Faure et al 2022;Robles et al 2023;Bendel et al 2023;Dibyachintan et al 2024). For example, a recent study showed the effect on binding of combining mutations in a PDZ domain and its binding motif (Zarin and Lehner 2024).…”
Section: Introductionmentioning
confidence: 99%